2020
DOI: 10.3389/fphar.2020.560920
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Jianpi Bushen Therapy for Treatment of CKD Anemia: A Meta-Analysis of Randomized Controlled Trials

Abstract: Objectives: To evaluate the efficacy of Traditional Chinese Medicine, specifically Jianpi Bushen (JPBS) therapy, for treatment of patients with chronic kidney disease (CKD) anemia. Methods: Randomized controlled trials of JPBS therapy for CKD anemia were searched and selected from seven electronic databases. The Cochrane collaboration tool was used to conduct methodological quality assessment. RevMan v5.3 software was utilized to perform data analysis. Results: In total, 12 randomized controlled trials with 79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Several studies have confirmed that traditional Chinese medicine (TCM), which has a long history, is safe and reliable for long-term treatment of patients with CKD [ 12 , 13 ]. According to TCM, the basic pathological feature of CKD is spleen-kidney deficiency, and qi stagnation and blood stasis is a key factor in the progression of CKD [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed that traditional Chinese medicine (TCM), which has a long history, is safe and reliable for long-term treatment of patients with CKD [ 12 , 13 ]. According to TCM, the basic pathological feature of CKD is spleen-kidney deficiency, and qi stagnation and blood stasis is a key factor in the progression of CKD [ 14 ].…”
Section: Introductionmentioning
confidence: 99%